2017
DOI: 10.32007/med.1936/jfacmedbagdad.v59i1.15
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase associated lipocalin (NGAL) in early detection of nephropathy in type 2 diabetic Iraqi patients

Abstract: Background: Diabetic nephropathy is a common complication of diabetes mellitus type2. The neutrophil gelatinase Associated lippocallin (NGAL) is an ubiquitous protein consist of 178 amino acid. NGAL can be identified in plasma and urine starting 2-4 hours after a kidney injury resulting changes in glomerular filtration and tubular reabsorption and with increased secretion in tubular epithelial cells. Objective: This study aimed to evaluate the role of serum Neutrophil Gelatinse Associated Lipocallin (NGAL) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…So, it is suggested the long duration of diabetes and poor glycemic control lead to increase NGAL in serum and urine. 26 Studies have suggested that there are two types of subclinical AKI. The first type can be detected in patients who never develop functional AKI with the disappearance of the structural after the exposure to the insult has stopped.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is suggested the long duration of diabetes and poor glycemic control lead to increase NGAL in serum and urine. 26 Studies have suggested that there are two types of subclinical AKI. The first type can be detected in patients who never develop functional AKI with the disappearance of the structural after the exposure to the insult has stopped.…”
Section: Discussionmentioning
confidence: 99%